Pixar short films collection. Volume 2 [videorecording (DVD)] - Capobianco, Jim; Capobianco, Jim; Capobianco, Jim; MacLane, Angus; MacLane, Angus; MacLane, Angus; Sohn, Peter; Sohn, Peter; Sohn, Peter; Del Carmen, Ronnie; Cooley, Josh; Cooley, Josh; et al. (Disney DVD., 2012)
Disney and Pixar present an incredible new collection of 12 short films, featuring multiple Academy Award nominees (best short film, animated: Presto, 2008; Day & Night, 2010; La Luna, 2011) and a host of family favorites. Join the celebration of imagination with this must-own collection, packed with unforgettable animation, fantastic stories, and captivating characters.